2016
DOI: 10.1126/sciadv.1501938
|View full text |Cite
|
Sign up to set email alerts
|

Long photoperiods sustain high pH in Arctic kelp forests

Abstract: In situ measurements and aquaria manipulation show that long summer days lead to sustained high pH in Arctic kelp forests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 54 publications
2
49
0
Order By: Relevance
“…Although experimental studies have shown soft calms to be susceptible to aragonite dissolution from acidification (Gazeau et al, ; Ries et al, ), it is difficult to say how those experiments relate to the natural environment that the clams actually live in. Other lines of research have shown that vulnerability to acidification also depends on food supply (Ramajo et al, ) and the ability for the surrounding habitat to regulate pH (e.g., Krause‐Jensen et al, ). Nevertheless, since our sampling coincides with the clam harvesting depth and was conducted during the season with expected minimum pH values, we felt it would be useful to report the calcium carbonate saturation states based on our measured carbon system parameters (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Although experimental studies have shown soft calms to be susceptible to aragonite dissolution from acidification (Gazeau et al, ; Ries et al, ), it is difficult to say how those experiments relate to the natural environment that the clams actually live in. Other lines of research have shown that vulnerability to acidification also depends on food supply (Ramajo et al, ) and the ability for the surrounding habitat to regulate pH (e.g., Krause‐Jensen et al, ). Nevertheless, since our sampling coincides with the clam harvesting depth and was conducted during the season with expected minimum pH values, we felt it would be useful to report the calcium carbonate saturation states based on our measured carbon system parameters (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the rate and amplitude of pH changes are inversely proportional to the spatial scale considered, i.e., small scale pH fluctuations can be fast (sec‐min) and dramatic (1–3 units) in the diffusive boundary layer of macroalgal thalli whereas large‐scale seasonal pH fluctuations in coastal waters are much slower (weeks‐months) and less strong (< 1 unit) (Wahl et al ). In addition, macroalgal photosynthesis may raise the mean pH in their vicinity, an effect which increases with increasing daily photoperiod (Krause‐Jensen et al ).…”
mentioning
confidence: 99%
“…The concept of chemical refuge has been raised in response to major concerns about the negative effects of OA on calcifying invertebrates (Buapet et al 2013;Greiner et al 2018;Groner et al 2018;Hendriks 2014;Krause-Jensen et al 2016;Unsworth et al 2012). In coastal ecosystems, macroalgal beds are characterised by intense metabolic activity capable of modifying their surrounding environment (Cornwall et al 2013(Cornwall et al , 2014Dayton 1985;Hofmann et al 2011;Hurd 2015).…”
Section: Macrophytes As Oa Refuges For Calcifying Marine Organismsmentioning
confidence: 99%